Structuring integrity: The impact of form partitioning on honesty in self-reports - Nhat Luong (Philipps-University Marburg, School of Business and Economics, 2023)
This study investigates the impact of visual and content-wise partitioning on the truthfulness of self-report forms. In all treatments of this experiment, participants have to report how many correct predictions they have made for five coin tosses. The only difference between treatments is the design of the report form. Contrary to certain literature, findings reveal that less partitioned or bureaucratic forms correlate with increased honesty. With its concise yet insightful results, this study is relevant for policymakers and researchers in designing self-reporting structures when honest reporting is essential.
Keywords: 330